Are you tripping comfortably? Investigating the relationship between harm reduction and the psychedelic experience - Madelene Palmer; Olivia M. Maynard (BMC, 2022)
Abstract Background Alongside a recent revival in the use of psychedelics in clinical settings, there have been increases in the prevalence of recreational use, with many using psychedelics to deal with difficult emotions or to improve well-being. While clinical research is conducted in carefully controlled settings, this is not necessarily the case for recreational use. In this mixed methods online survey study, we aimed to develop an understanding of frequently used psychedelic harm reduction practices in recreational settings and how their use relates to the psychedelic experience. We also aimed to characterise users' first and most recent psychedelic trips to understand how harm reduction changes with experience. Methods Participants (n = 163) recounted their first and most recent psychedelic experience by providing details about the harm reduction practices they employed and completing the Challenging Experience Questionnaire (CEQ) and Emotional Breakthrough Inventory (EBI). We also asked open-ended questions for a more in-depth qualitative understanding of their views on psychedelic harm reduction. Results Using ANOVA, we observe greater use of harm reduction practices for participants' most recent versus first psychedelic experience and that use of these practices is positively associated with EBI scores and negatively associated with CEQ scores (particularly for the first experience). Participants engaged in a wide range of harm reduction practices and we provide details of those which are most commonly used and those which are deemed most important by experienced users. Our qualitative analysis indicated that participants were largely positive about psychedelics and many recounted profound positive experiences. While specifics of the drug they were taking was important for aspects of harm reduction, participants largely focused on the importance of ensuring a good "set and setting" for enhancing positive effects. Conclusions Our research helps us understand how engagement in harm reduction may increase with experience. Our mixed methods data shed light on the perceived importance of different harm reduction practices and examine their association with the psychedelic experience itself. Together, our research has important implications for the development of psychedelic harm reduction advice and provides opportunities for future research to explore the importance of these different practices in more detail.